Determinants of Tax Arrears Revenue at the Surabaya Mulyorejo Primary Tax Service Office: Deterrent Effect of Taxpayers on Auction Announcement - Yanto, Alif Faruqi Febri; Izzalqurny, Tomy Rizky; Ilhamy, Mochammad (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to analyze the determinants of tax arrears revenue at the Surabaya Mulyorejo Primary Tax Service Office, with a focus on the deterrent effect of taxpayers on auction announcements. This study uses a quantitative approach by examining variables such as warning letters, forced letters, and confiscation warrants. Data were obtained from the annual report of KPP Pratama Surabaya Mulyorejo, with the observation period from 2019 to 2023. The results showed that warning letters, Billing with Forced Letters, warrant to carry out confiscation and auction announcements have a significant effect on the receipt of tax arrears. The implication of this study shows that stricter law enforcement can increase taxpayer compliance and reduce tax arrears. This study aims to analyze the determinants of tax arrears revenue at the Surabaya Mulyorejo Primary Tax Service Office, with a focus on the deterrent effect of taxpayers on auction announcements. This study uses a quantitative approach by examining variables such as warning letters, forced letters, and confiscation warrants. Data were obtained from the annual report of KPP Pratama Surabaya Mulyorejo, with the observation period from 2019 to 2023. The results showed that forced letter, confiscation order, and auction announcement letter have a significant effect on the receipt of tax arrears. Stricter law enforcement can increase taxpayer compliance and reduce tax arrears.